Studi Living Qur`An: Tradisi Khatam Al-Qur`An Pada Kematian Di Desa Lebuh Lurus Kecamatan Inuman Kabupaten Kuantan Singingi Provinsi Riau - Junita Junita; Yusrizal Efendi (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2023)
The people of Lebuh Lurus Village, Inuman District, Kuantan Singingi Regency, Riau Province have a habit of performing khatam al-Qur`an at death. The focus of this research is: (1) what is the history of the khatam al-Qur`an tradition at death, (2) how is the practice of the khatam al-Qur`an tradition at death, and (3) what is the meaning of the khatam al-Qur`an tradition and in death for the local community. This type of research is field research with the Living Qur'an approach and is descriptive in nature. While the data collection techniques used are interviews, observation and documentation. The research results that have been obtained are (1) The tradition of khatam al-Qur`an at death in Lebuh Lurus Village is a tradition of the Syattariyah Order, whose history dates back to the time of Abdul Ra'uf Singkel (1615-1693 AD). One of his students was Sheikh Imam Saleh (1848-1933 AD) who spread this tradition in Inuman District. However, finally arriving in Lebuh Lurus Village, it was brought and developed by Ustadz Muhammad Thohir (1928-1991). recited 30 chapters of the Qur'an together for six consecutive nights. (3) This tradition is a form of action that is seen as good, so that it has a reciprocal effect of kindness on readers and people who have died, because they will get a reward from what is read.